Millimeter-wave 3D printing metasurface filtering crossover based on a single groove gap waveguide cavity - Hongtao Gu; Jinxuan Ni; Xin Zhou; Jingyi Zhang; Gang Zhang; Jiquan Yang (Materials & Design)
A millimeter-wave (mm-wave) 3D-printing metasurface filtering crossover based on groove gap waveguide (GGW) structure is proposed in this letter. Firstly, the metasurface composed of electromagnetic bandgap elements in GGW technology is designed and analyzed. This configuration effectively mitigates radiation and electromagnetic wave leakage. The upper part of the GGW resonator features a groove structure with periodic pins distributed, while the lower part consists of a metal groove structure. Subsequently, by incorporating resonant irises, the device order and bandwidth are increased. Transmission zeros (TZ) is generated by cross-coupling between the GGW resonator and source. Furthermore, by adding an L-shaped capacitive stub at one end of each port, another TZ is created, further enhancing the frequency selectivity of the filtering crossover. To verify the design, a third-order filtering crossover operating in the Ka band is fabricated using 3D printing technology. The measured results show excellent agreement with the simulations. The final filtering crossover achieves a 3-dB fractional bandwidth of 4.8 %, a return loss better than 19.5 dB, and an in-band isolation greater than 32 dB.